Stimulation and cognitive function in short-stature preschoolers - Ika Citra Dewi; Rini Sekartini; Hartono Gunardi; Asrawati Nurdin (Indonesian Pediatric Society, 2021)
Background Normal-height children generally have better cognitive function than growth-stunted, short-stature children. Children’s cognitive function reportedly improves with stimulation. However, a correlation between stimulation and cognitive function in children with a history of short stature remains unclear. Objective To assess correlation between stimulation and cognitive function in normal-height vs. short-stature preschool children. Methods A cross-sectional study with consecutive sampling was performed in four sub-district areas in Jakarta. Preschool-aged children and their primary caregivers from previous studies on short stature were eligible for inclusion. An Indonesian version of a questionnaire was used to assess stimulation. A psychologist assessed verbal IQ (VIQ), performance IQ (PIQ), and full-scale IQ (FSIQ) with the Indonesian version of the Wechsler Preschool and Primary Scale of Intelligence (WPPSI). Data were analyzed using Pearson’s correlation and Chi-square tests, and P values <0.05 were considered to be significant. Results Of 62 subjects, 64.5% had normal height and 35.5% had short stature. Both normal-height and short-stature children had similar IQ outcome and history of stimulation. The stimulation was significantly correlated with FSIQ in normal-height children (r= 0.316; P=0.047), but not short-stature children (r=0.049; P=0.828). However, the percentage differences in VIQ, PIQ, and FSIQ between normal-height and short-stature children were not significant (P=0.409, 0.119 and 0.877, respectively). Conclusion There is a significant correlation between stimulation and IQ in normal-height children. Short-stature preschoolers were not worse in terms of IQ than normal-height preschoolers. Parents and caregivers should be encouraged to provide regular and adequate stimulation to their young children.